Evaluación de la superficie de la estructura adamantina luego de la remoción de la resina residual al descementado de brackets - Coronel Cevallos, Tatiana Cecivel (2019)
In the Orthodontics, when presenting the apparatus with a perfect union to the tooth, it is necessary to preserve the tooth enamel to the maximum when it is removed. The enamel must have the same conditions as at the beginning, however, there may be damage such as cracks or fractures which are evident under a microscope, so it is sought to use appropriate instruments to minimize these alterations. Objective: To evaluate the damage caused to the adamantine structure after polishing the residual resin present on the enamel surface, between two types of rotary instruments. Materials and methods: a total of 40 dental pieces were used between incisors, canines and permanent premolars that were randomly divided into two groups (n = 20) Group A and B; Arkansas stone burs and multilaminate of pointed conical tungsten carbide (24 sheets) were used. Each specimen was observed through a Stereomicroscope (UNICO binocular, Model ZM181HF, 10X magnification eyepieces, and 6.7.1 zoom) in two stages, by ESI-i and ESI-f before cementation and after polishing of the residual resin. Results: Arkansas stone burs polishing obtained 55% of dental pieces in ESI-f 4, an unacceptable surface; compared to the multi-laminated tungsten carbide milling cutter that obtained 45% in ESI-f 2, an acceptable surface. It was concluded that multi-laminated burs caused minor damage, reached an average of final surface index 2 (acceptable). Keywords: enamel damage, initial-final enamel surface, Arkansas stone, multi-laminated burs.